2011
DOI: 10.1021/bi200015h
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-2 Regulation of the cAMP Response Element Binding Protein

Abstract: Previous work demonstrated that cystic fibrosis (CF) cells exhibit an increase in cAMP-mediated signaling as a characteristic response to lost CFTR function. Evidence for increased cAMP-mediated signaling in CF included increased phosphorylation of the cAMP response element binding protein (CREB) and elevated β-arrestin-2 (βarr2) expression. However, subsequent studies reveal that CREB activation in CF cells is independent of protein kinase- A (PKA). The goal of this study is to test the hypothesis that elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Interestingly, all ligands are ϳ30 -100-fold less potent to stimulate CRE activity in comparison to recruiting ␤-arrestins, which might suggest that ␤-arrestin is not involved in CRE activation in PTX-treated CCX-CKR-expressing cells by interacting with the transcription factor cAMPresponse element-binding protein and the histone acetyltransferase p300 as previously observed for the ␦-opioid receptor (43). Moreover, the absence of CCL19-induced ERK1/2 phosphorylation in CCX-CKR-expressing cells indicates that CRE activation is also not induced via a ␤-arrestin-and ERK1/2-dependent pathway, which has been recently described in tracheal epithelial cells (44). FIGURE 9.…”
Section: Figure 8 Potentiation Of Ccx-ckr-mediated Cre Activation Issupporting
confidence: 69%
“…Interestingly, all ligands are ϳ30 -100-fold less potent to stimulate CRE activity in comparison to recruiting ␤-arrestins, which might suggest that ␤-arrestin is not involved in CRE activation in PTX-treated CCX-CKR-expressing cells by interacting with the transcription factor cAMPresponse element-binding protein and the histone acetyltransferase p300 as previously observed for the ␦-opioid receptor (43). Moreover, the absence of CCL19-induced ERK1/2 phosphorylation in CCX-CKR-expressing cells indicates that CRE activation is also not induced via a ␤-arrestin-and ERK1/2-dependent pathway, which has been recently described in tracheal epithelial cells (44). FIGURE 9.…”
Section: Figure 8 Potentiation Of Ccx-ckr-mediated Cre Activation Issupporting
confidence: 69%
“…These cells also show a colocalization of the expressed ␤ arr2-GFP and unesterifi ed cholesterol. Previous studies demonstrated that total ␤ arr2 expression in ␤ arr2-GFP cells was comparable to CF model cells ( 22 ).…”
Section: Cholesterol Processing In ␤ Arr2-overexpressing Cellsmentioning
confidence: 82%
“…Cftr/ ␤ arr2 double knockout (DKO) mice were developed as recently published ( 22 ) and utilized to directly examine the effect of ␤ arr2 on aspects of cholesterol processing and signaling. We previously demonstrated that CF mice exhibit increased de novo cholesterol synthesis in the liver compared with sibling WT mice ( 11 ).…”
Section: Effect Of In Vivo Depletion Of ␤ Arr2 Expression In Cftrmentioning
confidence: 99%
“…Nasal epithelium excised from Cftr and β-arrestin 2 double knockout mice exhibit reduced pCREB and pERK levels compared to Cftr −/− mice, but similar to WT mice. Thus, β-arrestin 2 directly regulates cystic fibrosis induced CREB activation through the ERK signaling pathway 164 .…”
Section: Role Of β-Arrestins In Human Diseasesmentioning
confidence: 99%